Caracterização química e determinação da atividade antioxidante in vitro e in vivo de frações polissacarídicas extraídas a partir de subprodutos agroindustriais de frutas tropicais - Sabino, Luiz Bruno de Sousa (2015)
The aim of this work was to characterize the chemical structure and investigate the antioxidant activity in vitro and in vivo of polysaccharide fractions extracted from by-products of acerola, pineapple, cashew, mango and passion fruit processing. Using the exhaustive aqueous extraction, a greater mass yield was obtained for the polysaccharide fraction extracted of the mango by-product (20%) which was higher than that from the pineapple and acerola at 96 and 87%, respectively. The infrared spectra showed typical assignment of polysaccharides chemical groups such as OH (3000 - 3500 cm -1),CO (1034 cm-1), C-O-C (1150 cm-1) and H-C1 (1079, 929 and 858 cm-1). 13C-NMR signals at δ 170.6 and 100, present in all material, indicated the presence of uronic and galacturonic acid, respectively, showing the nature of such pectin. High molecular weight was assigned to the fraction obtained of mango by-product (1.54 x 10 6 g/mol) followed by passion fruit (3.69 x 10 5g / mol) and acerola, pineapple and cashew (~10 4g/ mol). The protein content ranged from 0.25 (pineapple) to 0.68% (cashew), agreeing with the evidenced by the infrared spectrum which is 1242 cm-1 for these molecules. Major total antioxidant activity and minor IC 50 were observed for the polysaccharide fraction of cashew (147 ± 4.1 μM Trolox/g and 0.03 mg/mL,respectively). The fractions obtained from acerola, pineapple, passion fruit (IC50 = 0,05 mg/mL) and mango (IC50= 0.33 mg/mL) also had low IC50, indicating the efficiency of these materials in the elimination of ABTS•+ radical in low concentrations. The MTT assay indicated that no toxicity of the polymeric fractions studied even when evaluated at concentrations of 100%. The total antioxidant activity in vivo showed that materials prevenient of acerola, pineapple and cashew were efficient (p <0.05) in maintaining the levels of GSH and MDA reduction in gastric tissue of rats stressed with ethanol 50%. The polysaccharides fractions of mango and passion fruit exhibited less satisfactory results in both antioxidants tests, which may be assigned to its high molecular weight and viscosity. Together, the results presented in this study, showed that the polysaccharide fractions extracted from byproducts studied had pectic nature in association with proteins, which highlighted, especially for those taken from the cherry, pineapple and cashew, effective antioxidant action in vitro and in vivo, suggesting their possible application as natural antioxidants.